2014
DOI: 10.1177/2047487314563447
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake, hypertension development and mortality in black South Africans

Abstract: GGT independently predicted cardiovascular and all-cause mortality, as well as hypertension development in black South Africans. Despite non-specificity to excessive alcohol consumption, GGT may be a useful general marker for hypertension development and mortality, also due to its significant association with self-reported alcohol intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
3
24
5
Order By: Relevance
“…Also, alcohol consumption, a well-known risk factor of HTN (15) was not significantly reported in our analyses. In other sub-Saharan African studies results are also controversial, showing either association, or no significant association between HTN and moderate to heavy alcohol consumption (27,28). Furthermore, our study suggests a slightly protective effect of the light alcohol consumption in men, probably as the reflect of a healthy lifestyle.…”
Section: Discussioncontrasting
confidence: 79%
“…Also, alcohol consumption, a well-known risk factor of HTN (15) was not significantly reported in our analyses. In other sub-Saharan African studies results are also controversial, showing either association, or no significant association between HTN and moderate to heavy alcohol consumption (27,28). Furthermore, our study suggests a slightly protective effect of the light alcohol consumption in men, probably as the reflect of a healthy lifestyle.…”
Section: Discussioncontrasting
confidence: 79%
“…The results from sub-Saharan African studies on the risk relationship between alcohol consumption and hypertension are mixed; some studies, primarily in South Africa, observed an association [36], while other studies emanating from other sub-Saharan African countries observed no significant association [37]. All these studies are hardly comparable since the setting, the assessment mode of alcohol consumption assessment age at inclusion are different.…”
Section: Discussionmentioning
confidence: 61%
“…Many factors have been associated with the development of hypertension, such as an elevated body mass index, occupation, socioeconomic status, tobacco use, abdominal obesity, physical activity, and alcohol consumption, among others [5,48,51]. Many studies have reported a positive, dose-dependent association between alcohol intake and hypertension, showing the J-shaped curve also described for overall cardiovascular effects [5,16,19,22,[52][53][54][55][56]. Excessive alcohol consumption accounts for about 16% of cases of hypertension worldwide [5,57].…”
Section: Hypertensionmentioning
confidence: 99%
“…Accurate estimations of alcohol consumption can be challenging. The most frequent way to address this issue is by self-reporting, which inherently involves the possibility of under-or overestimating intake depending on the social perceptions of the individual [16][17][18]. Moreover, serum markers of alcohol intake have been identified, mainly gamma-glutamyltransferase (GGT).…”
Section: Introductionmentioning
confidence: 99%